1973
DOI: 10.1159/000460348
|View full text |Cite
|
Sign up to set email alerts
|

Blood Groups of Mountain Gorillas (Gorilla gorilla beringei)

Abstract: Blood and saliva from two mountain gorillas have been tested for human-type A-B-H, M-N and Rh-Hr blood groups as well as for homologues of the chimpanzee V-A-B and C-E-F systems. Both animals proved to be group B, and in this respect as well as in the other tests their red cells exhibited no apparent differences from the red cells of lowland gorillas previously tested by us.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…In tests for homologues of the human M‐N types [5], the red cells of all four mountain gorillas gave positive reactions with anti‐N v lectin (Vicia graminea and Vicia unijuga) ; one rabbit anti‐N serum also agglutinated their red cells but a second rabbit antiserum failed to do so. Similar reactions had been obtained with the red cells of the two mountain gorillas previously reported [4] as well as from all the lowland gorillas [5] indicating that all gorillas have an N‐like agglutinogen on their red cells. Tests on the red cells of the four new mountain gorillas with several anti‐M rabbit antisera gave strong positive reactions as in the case of the two mountain gorillas previously reported.…”
Section: Human‐type Blood Groupssupporting
confidence: 85%
See 2 more Smart Citations
“…In tests for homologues of the human M‐N types [5], the red cells of all four mountain gorillas gave positive reactions with anti‐N v lectin (Vicia graminea and Vicia unijuga) ; one rabbit anti‐N serum also agglutinated their red cells but a second rabbit antiserum failed to do so. Similar reactions had been obtained with the red cells of the two mountain gorillas previously reported [4] as well as from all the lowland gorillas [5] indicating that all gorillas have an N‐like agglutinogen on their red cells. Tests on the red cells of the four new mountain gorillas with several anti‐M rabbit antisera gave strong positive reactions as in the case of the two mountain gorillas previously reported.…”
Section: Human‐type Blood Groupssupporting
confidence: 85%
“…Similar reactions had been obtained with the red cells of the two mountain gorillas previously reported [4] as well as from all the lowland gorillas [5] indicating that all gorillas have an N-like agglutinogen on their red cells. Tests on the red cells of the four new mountain gorillas with several anti-M rabbit antisera gave strong positive reactions as in the case of the two mountain gorillas pre viously reported.…”
Section: Human-type Blood Groupssupporting
confidence: 82%
See 1 more Smart Citation
“…All gorillas tested, whether mountain or lowland, have proved to be group B, although their red cells fail to agglu tinate with anti-B reagents [11]. Tests on the saliva showed that all anthro poid apes examined were A-B-H secretors in conformity to their blood groups, except for a single orangutan.…”
mentioning
confidence: 96%
“…In comparison to lowland gorillas, access to clinical samples from mountain gorillas has never been widely available for blood group determination. Initially, no reported differences were noted between lowland and mountain gorilla ( n = 2) blood group assessment [Socha et al, 1973]. However, one researcher—and a coauthor in the lowland gorilla study—consistently remarked that mountain gorillas were similarly nonreactive as the lowland species when blood was utilized, but were group A on secretor status [Weiner and Gordon, 1960; Wiener et al, 1963].…”
Section: Discussionmentioning
confidence: 99%